The effect of solvent swelling pre-treatment on Mukah Balingian Malaysian low rank coal on pyrolysis and liquefaction processes/ Mohd Fauzi Abdullah - Abdullah, Mohd Fauzi (2007)
Swelling properties of Mukah Balingian (MB) coal with various H-bonding (i.e. pyridine, tetrahydrofuran (THF), acetone, ethanol and methanol), non-hydrogen bonding (i.e. tetralin, n-hexane, cyclohexane and toluene) was investigated using volumetric swelling ratio method. A higher rank Silantek (SL) coal was used as a comparison study. In general, H-bonding solvents exhibit higher swelling ratio in the coal than the non-H-bonding solvents with pyridine being the best swelling solvent. Swelling ratio of MB coal in all solvents gave higher values than SL coal due to low cross-link density and smaller size of aromatic ring cluster that exhibit in low rank coal. The coal macrostructure of the swelled MB coal samples showed some changes when swelled with H-bonding solvents as showed through SEM micrographs. In addition, the swelling ratios of the MB coal with mixed of tetralin with the other Hbonding solvents at volume ratio of 20:80, 40:60, 60:40 and 80:20 were decreased with increased in the volume ratios of tetralin. This is probably attributed to the less interaction of the coal reactive sites with the solvent due to its non-hydrogen bonding characteristics. Furthermore, the thermal behaviours and kinetic properties of untreated and pre-treated swelled samples during pyrolysis were determined using therraogravimetric analyzer (TGA). The thermal behaviour of pure and mixed swelled samples that were represented by DTG curve showed some changes on coal macrostructure had occurred during swelling process. In general, the overall activation energy and pre-exponential factor of solvent-swelled samples at second stage pyrolysis (i.e. 200 to 700°C) that were determined using the first-order kinetic reaction model showed lower values in comparison to the untreated coal due to the bond weakening of the coal macromolecular interaction network of the former. Interestingly, in all cases, the mixed solvent swelled samples exhibit much lower activation energy and higher organic volatile matter in comparison to untreated and pure solvent-swelled coal samples indicating an increased in reactivity of the coal during swelling, The liquefaction on acetone-swelled sample that was carried out at 4 MPa and 420°C showed higher coal conversion and oil+gas yield in comparison to the untreated coal. This finding was due to the enhancement of coal macropores and solvent-coal interactions during the swelling process that promote the releasing of volatile matter at lower temperature. The highest oil+gas yield was obtained with 20%tetralin:80%acetone mixed solvent-swelled sample when liquefaction was carried out at less severe condition (i.e. 4 MPa and 420°C). These findings seem to agree with the thermal behaviour and kinetic properties of the 20%tetralin:80%acetone mixed solvent-swelled sample during pyrolysis that showed the lowest activation energy with high organic volatile matter yields indicating an increased in coal reactivity. Thus, these phenomena proved the beneficial effect of swelling pre-treatment on coal in enhancing oil yield prior to liquefaction at less severe condition. Thus far, the characteristics coal liquefaction residue (CLR) study showed that it had potential to be a good feedstock for gasification and combustion processes.